FibroScan predicts ascites after liver resection for hepatitis B virus-related hepatocellular carcinoma: A prospective cohort study. (August 2015) - Li, Chuan; Zhang, Jing-Yi; Zhang, Xiao-Yun; Wen, Tian-Fu; Yan, Lu-Nan
Abstract: Objective: To assess the correlation of preoperative FibroScan value and postoperative ascites in patients undergoing liver resection for hepatitis B virus-related hepatocellular carcinoma (HBV-related HCC). Methods: A prospective study group of consecutive HBV-related HCC patients considered eligible for liver resection was conducted from 2012 to 2014 (N = 77). Liver stiffness measured by FibroScan was administrated to all patients. Patient's pre- and intra-operative variables were prospectively collected. Results: FibroScan was successfully performed in 75 patients. Postoperative ascites was observed in 13 patients. Univariate analyses suggested tumor size, high preoperative hepatitis B viral load, intraoperative blood loss, major hepatectomy and FibroScan value were potential risk factors for postoperative ascites. However, in multivariate analysis, only FibroScan value (OR = 1.506, 95%CI = 1.21–1.87) showed prognostic power. The best cut-off value of FibroScan value to predict postoperative ascites was 15.6 kpa with a sensitivity of 76.9% and a specificity of 98.4%. The corresponding area under the receiver operating curve was 0.902. Conclusions: FibroScan value was a reliable surrogate marker for predicting postoperative ascites should be routinely performed in patients with HBV-related HCC undergoing liver resection. Highlights: Ascites was not uncommon following liver resection for HCC. Liver stiffness measured by Fibroscan is a predictor of postoperative ascites after liver resection. Liver stiffness measured by Fibroscan may be a useful predictor of postoperative liver failure.